The Location of the UK Cotton Textiles Industry in 1838: a Quantitative Analysis - Nicholas Crafts; Nikolaus Wolf (European Historical Economics Society (EHES), 2013)
We examine the geography of cotton textiles in Britain in 1838 to test claims about why the industry came to be so heavily concentrated in Lancashire. Our analysis considers both first and second nature aspects of geography including the availability of water power, humidity, coal prices, market access and sunk costs. We show that some of these characteristics have substantial explanatory power. Moreover, we exploit the change from water to steam power to show that the persistent effect of first nature characteristics on industry location can be explained by a combination of sunk costs and agglomeration effects.
Keywords: N63; N93; R12; 330; agglomeration; cotton textiles; geography; industry location